The Use of Cultural Filter to Achieve Functional Equivalence in English – Indonesian Translation of Dindal’s Chicken Little: The Sky is Falling - Karismawati, Angga; Yuliasri, Issy; Hartono, Rudi (English Education Journal, 2021)
The study aims to explain the implementation of cultural filter through the House’s dimensions (2015), as well as to explain the achievement of functional equivalence of children comic Chicken Little: The Sky is Falling. This study belongs to descriptive qualitative study. The research was conducted by analyzing the dimensions of directness versus indirectness, orientation towards other versus orientation towards self, orientation towards addressees versus orientation towards content, implicitness versus explicitness, verbal routines versus ad-hoc formulation. The findings reveal that there are 190 cultural filters found within the comic. There are 111 from orientation towards addressees versus orientation towards content, implicitness versus explicitness are 31, directness versus indirectness are 30, verbal routines versus ad-hoc formulation are 15, and the last is 3 from orientation towards other versus orientation towards self. On the other hand, out of 190, 15 sentences are identified as non-equivalence. In accordance with the result, the translator successfully applies cultural filter in order to reduce the cultural gap between SL and TL. Besides, the findings also suggest that cultural filter supports the achievement of functional equivalence of the translation.